Truman the dog ebook - Florence, Debbi Michiko (My Furry Foster Family, 2019)
"T" is for Truman, tricks, and TROUBLE! Truman the black lab might be an older rescue dog, but he's still got enough mischief beneath his collar to keep eight-year-old Kaita Takano and her animal-fostering family on their toes from morning till night. Chewed through and through, the playfully illustrated, Kaita-narrated chapter book promises plenty of canine fun.